Primary Market Design: Direct Mechanisms and Markets - Alex Stomper; Pegaret Pichler (Fondazione Eni Enrico Mattei (FEEM), 2004)
We develop a model that allows for the coexistence of bookbuilding and when-issued trading. We show that, due to interactions between these two processes, allowing for when-issued trading is for the most part beneficial for issuers. When-issued trading may interfere with information gathering thorough bookbuilding, in the case that informative bookbuilding is not needed. However, informative bookbuilding may be a prerequisite for the when-issued market to function. In this case the existence of a liquid when-issued market will not interfere with information gathering through bookbuilding, and will strictly benefit the issuer.
Keywords: G32; 330; Initial public offerings; Information gathering mechanisms; When-issued trading; Börsengang; Informationsversorgung; Emissionskurs